2020
DOI: 10.3390/ijerph17197174
|View full text |Cite
|
Sign up to set email alerts
|

Association between Migrant Women’s Legal Status and Prenatal Care Utilization in the PreCARE Cohort

Abstract: Barriers to access to prenatal care may partially explain the higher risk of adverse pregnancy outcomes among migrants compared with native-born women in Europe. Our aim was to assess the association between women’s legal status and inadequate prenatal care utilization (PCU) in France, where access to healthcare is supposed to be universal. The study population was extracted from the PreCARE prospective cohort (N = 10,419). The associations between women’s legal status and a composite outcome variable of inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Differences in how immigrants are defined in each society, as well as the legal status of the immigrant population may be a challenge to access healthcare services. These may be extrapolated to prenatal care utilization, both by its timing and its content [ 163 ], which subsequently impact on the risk of adverse outcomes among pregnant women with the immigration background. Additionally, it is argued that misconceptions between healthcare providers and immigrant women through different cultural concepts and acceptability of care, or more directly through lack of interpretation services may affect pregnancy outcomes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in how immigrants are defined in each society, as well as the legal status of the immigrant population may be a challenge to access healthcare services. These may be extrapolated to prenatal care utilization, both by its timing and its content [ 163 ], which subsequently impact on the risk of adverse outcomes among pregnant women with the immigration background. Additionally, it is argued that misconceptions between healthcare providers and immigrant women through different cultural concepts and acceptability of care, or more directly through lack of interpretation services may affect pregnancy outcomes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of a poor understanding of information among refugees may partially explain insufficient access and utilisation of antenatal care within this subgroup of migrants [ 4 , 41 ]. The majority language proficiency is undoubtedly an important factor in understanding information, as confirmed by other studies [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in maternal health outcomes and sub-optimal healthcare for migrants in Europe have been well documented [ 2 , 3 ]. Migrants have poorer access to, and inadequate utilisation of, available maternity healthcare services, which may be associated with socioeconomic status and the reason for migration [ 4 ]. Furthermore, women born in low- or middle-income countries represent a group with a higher risk-profile and in need of healthcare during pregnancy and birth [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis that might explain this result is that antenatal care utilisation was inadequate in both quantity and quality. A previous analysis of this study has reported this inadequacy to be more prevalent among undocumented women 27 . This higher risk of inadequate antenatal care utilisation might be explained by the shorter residence and the greater frequency of linguistic barriers, social isolation and poor housing conditions among these women, compared with other categories of migrants.…”
Section: Discussionmentioning
confidence: 47%